2002
DOI: 10.1007/s00726-001-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phosphatidylcholine synthesis is associated with excitotoxic cell death in cerebellar granule cell cultures

Abstract: Glucose deprivation (GD) enhances the sensitivity of cerebellar granule cells to die by excitotoxicity. Neither 70 min of GD, a treatment that depletes cell energy resources, nor exposure to 20 microM glutamate (GLU) for 30 min, induce significant cell death in cultures of cerebellar granule cells. However, the combined treatment with GLU and GD induces choline (Cho) release before excitotoxic cell death. We investigated whether the neurotoxic effect of this treatment is related with inhibition of phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Choline kinase and CTP:phosphocholine cytidylyltransferase, the enzymes that catalyze the sequential conversion of Cho into phosphocholine and CDP-choline require ATP and CTP, respectively. Indeed, treatments that deplete cell energy resources, e.g., glucose deprivation, elicit a marked decrease in choline kinase activity (Gasull et al, 2002). In cortical cells, neurotoxic concentrations of NMDA produce a timedependent reduction of cell energy resources that may reach a 20% decrease of cell energy charge 30 min after treatment (Ankarcrona et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Choline kinase and CTP:phosphocholine cytidylyltransferase, the enzymes that catalyze the sequential conversion of Cho into phosphocholine and CDP-choline require ATP and CTP, respectively. Indeed, treatments that deplete cell energy resources, e.g., glucose deprivation, elicit a marked decrease in choline kinase activity (Gasull et al, 2002). In cortical cells, neurotoxic concentrations of NMDA produce a timedependent reduction of cell energy resources that may reach a 20% decrease of cell energy charge 30 min after treatment (Ankarcrona et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that inactivation of PC increased apoptosis and the cause of apoptosis linked with accumulation of the PC precursor, CDP-choline (Cui et al, 1996;Gasull et al, 2002;Williams et al, 1998). This is in line with our observation of pct1∆ being less hypersensitive to bee venom treatment compared to cpt1∆ and ept1∆ (Figure 4.2B) as Pct1p catalyses the reaction of choline phosphate and CDP to form CDP-choline (Ejsing et al, 2009).…”
Section: Lro1psupporting
confidence: 91%
“…The inhibition of PtdCho synthesis is accompanied by a decrease in the incorporation of [ 3 H]choline ([ 3 H]Cho) into phosphocholine and by an increase of the intracellular content of free [ 3 H]Cho, indicating that these treatments inhibit the synthesis of PtdCho by inhibiting choline kinase activity (Gasull et al, 2002). The inhibition of PtdCho synthesis is accompanied by a decrease in the incorporation of [ 3 H]choline ([ 3 H]Cho) into phosphocholine and by an increase of the intracellular content of free [ 3 H]Cho, indicating that these treatments inhibit the synthesis of PtdCho by inhibiting choline kinase activity (Gasull et al, 2002).…”
Section: Effects Of Glutamate On Glycerophospholipid Synthesismentioning
confidence: 99%